Standard specification for steel castings, iron-chromium and iron chromium-nickel, heat resistant, for general application. (American Society for Testing and Materials, 2008)
This specification covers standards for iron-chromium and iron-chromium-nickel alloy castings of general purpose grades (Grades HF, HH, HI, HK, HE, HT, HU, HW, HX, HC, HD, HL, HN, and HN) applicable in heat-resistant services. Alloys shall be produced through electric arc, electric-induction, or other approved processes. Heat-treatment shall be conducted when agreed upon by the manufacturer and purchaser. The material shall conform to carbon, manganese, silicon, phosphorus, sulfur, chromium, nickel, and molybdenum contents. Tensile requirements including tensile strength, yield point, and elongation shall apply when specified in the purchase order. Guidelines for repair by welding are also given.